ANALISIS MISKONSEPSI SISWA PADA MATA PELAJARAN IPA DI SMPN 4 PENUKAL UTARA KABUPATEN PENUKAL ABAB LEMATANG ILIR PENDOPO - Yulia Tri Samiha; Erie Agusta; Gestri Rolahnoviza (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study titled analysis misconceptions students use science subjects in SMPN 4 penukal utara kabupaten penukal abab lematang ilir pendopo. Misconceptions in students often happens, the misconception occurs because the need for students to understand a concept, as happened to the students at SMPN 4 penukal. This study aims to analyze student misconceptions in science subjects in SMPN 4 penukal utara kabupaten penukal abab lematangilir. According Omrood (2008) misconception is the belief that is not in accordance with generally accepted explanation and proved valid about a phenomenon or event. The research methodology used in this research is quantitative descriptive. Sampling using cluster random sampling, to be sampled VII.1 class research amounted to 38 students .Instruments used in the study using a multiple-choice test reasoned open. The analysis showed that there was a misconception in science subjects, namely on the material characteristics of living things and the organization of life. Percentage of misconceptions students on the material characteristics of living things at 41.5% for the material organization of life 48%. t can be concluded that student misconceptions in the material organization of life is higher than the misconceptions on the material characteristics of living things. Student misconceptions caused by student learning, the methods used, and the lack of students in finding information.